2022
DOI: 10.1200/op.21.00624
|View full text |Cite
|
Sign up to set email alerts
|

All You Need to Know About UGT1A1 Genetic Testing for Patients Treated With Irinotecan: A Practitioner-Friendly Guide

Abstract: Irinotecan is an anticancer agent widely used for the treatment of solid tumors, including colorectal and pancreatic cancers. Severe neutropenia and diarrhea are common dose-limiting toxicities of irinotecan-based therapy, and UGT1A1 polymorphisms are one of the major risk factors of these toxicities. In 2005, the US Food and Drug Administration revised the drug label to indicate that patients with UGT1A1*28 homozygous genotype should receive a decreased dose of irinotecan. However, UGT1A1*28 testing is not ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 60 publications
2
33
1
5
Order By: Relevance
“…In view of the available evidence and the convenience of commercial test ( 46 ), we recommend testing UGT1A1 in CRC patients who will undergo irinotecan-based chemotherapy and increasing the dose of irinotecan in patients with UGT1A1 *28 wild-type or heterozygous variant to improve clinical efficacy, which is consistent with the Pan-Asian adapted European Society for Medical Oncology consensus guidelines ( 47 ) and the latest comments of Karas et al. ( 48 ). It can be applied directly with the recommended MTD or gradually increased from routine dose to MTD by chemotherapy cycle based on safety considerations.…”
Section: Discussionsupporting
confidence: 62%
“…In view of the available evidence and the convenience of commercial test ( 46 ), we recommend testing UGT1A1 in CRC patients who will undergo irinotecan-based chemotherapy and increasing the dose of irinotecan in patients with UGT1A1 *28 wild-type or heterozygous variant to improve clinical efficacy, which is consistent with the Pan-Asian adapted European Society for Medical Oncology consensus guidelines ( 47 ) and the latest comments of Karas et al. ( 48 ). It can be applied directly with the recommended MTD or gradually increased from routine dose to MTD by chemotherapy cycle based on safety considerations.…”
Section: Discussionsupporting
confidence: 62%
“…Many studies have shown that, besides tumor-specific genes, individual genetic variations can also act as important predictors of tumor response and toxicity when treating patients with antitumor agents. For instance, with irinotecan treatment, up to 50% of Western patients with the UGT1A1*28 allele suffered from severe neutropenia [ 3 , 4 ], and these findings led to the recommendation to consider a reduced initial dose for patients known to be homozygous for the UGT1A1*28 allele. As such, it is very important to understand ethnic differences between genotypes for the development of predictive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Because neutropenia and diarrhea are the major toxicities associated with irinotecan chemotherapy, inherited differences in UGT1A polymorphisms affecting its activity may exert an important influence on the pharmacokinetics, toxicity, and pharmacologic effects of irinotecan. Some of these isoforms have been shown to have clinical significance for SN-38 glucuronidation and irinotecan-related toxicity; in particular, the low-activity UGT1A1 isoform, UGT1A1*28 , is strongly associated with irinotecan-induced neutropenia [ 3 , 4 ], especially in Western populations. Some studies have suggested that UGT1A1*6 or UGT1A1*27 might be more important among Asian cancer patients treated with irinotecan [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these times of multimorbidity and multidrug prescription, it must be kept in mind that glucuronidation can be enhanced by CYP3A4 inducers, like a barbituric, phenytoin, rifampin, smoking, and inhibited by strong CYP3A4 or UGT1A1 inhibitors such as diazepam, AINES, estrogens, and antidepressants, depending on the substrate candidate for glucuronidation, making it relevant for pharmacogenetics management. 1 Karas and Innocenti 2 have written an elegant paper updating the UGT1A1 different polymorphisms and their impact on efficacy and toxicities, irinotecan dose adjustments, and guidelines, scientific societies, and regulatory agencies recommendations.…”
mentioning
confidence: 99%